MOBILITAS TENAGA KERJA DARI SEKTOR PERTANIAN KE SEKTOR NON PERTANIAN DI KECAMATAN LAWANG KABUPATEN MALANG - Setyo Sulistyono Wahyu Sulistyono (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2011)
To the effect this research to know happening influence factor its labouring mobility and knows labouring mobility aim of agricultural sektor go to non agricultural sektor at Lawang's district Baleful Regency. This research utilizes descriptive analisis qualitative where research to gather information about state an aught phenomena which is phenomena which is charged what marks sense at the moment research be done. Analysis results obtained that there are factors that affect labor mobility, among others: age of respondent, educational level, income, and number of dependents covered by the respondent. And, the direction of labor mobility dominated the trading sektor. Based on the results of research, the implications of this study need to increase the quality of human resources at this sektor, education and expertise in communities, and equitable distribution of mobility in an attempt to align the direction of development.